The dynamics of a frictionally-dominated Amazonian estuary - Asp,Nils Edvin (2012)
The hydrodynamics, morphology and sedimentology of the Taperaçu estuary were investigated. This is one of several estuaries located within the largest mangrove fringe in the world, bordering the Amazon region, subject to a macrotidal regime and regionally atypical negligible fresh water supply. The results reveal widespread sand banks that occupy the central portion of the estuarine cross-section. Well-sorted very fine sandy sediments of marine origin prevail. Shorter flood phases, with substantially higher current velocities, were observed in the upper sector of Taperaçu, as expected for a shallow, friction-dominated estuary. However, ebb domination can be expected for estuaries with large associated mangrove areas and substantial estuarine infilling, both of which situations occur on the Taperaçu. The tidal asymmetry favoring flood currents could be the result of the absence of an effective fluvial discharge. Furthermore, it was observed that the Taperaçu is connected by tidal creeks to the neighboring Caeté estuary, allowing a stronger flux during the flood and intensifying the higher flood currents. As a whole, the results have shown a complex interaction of morphological aspects (friction, fluvial drainage, connections with neighbor estuaries, infilling and large storage area) in determining hydrodynamic patterns, thus improving the understanding of Amazon estuaries.